Understanding Human Papillomavirus Vaccine Promotions and Hesitancy in Northern California Through Examining Public Facebook Pages and Groups - Zhang, Jingwen; Xue, Haoning; Calabrese, Christopher; Chen, Huiling; Dang, Julie H. T. (Frontiers in Digital Health, 2021)
HPV vaccination coverage among adolescents is lower in rural regions and remains under the 80% coverage goal by Healthy People 2030. Through both sentiment analysis and topic modeling, this research examines how local health agencies and groups in nine Northern California counties promote HPV vaccines through Facebook, and how target populations react to promotion posts in comments that elucidate their sentiments and hesitancy toward HPV vaccination. In January 2021, we identified 2105 public Facebook pages and 1065 groups related to health within the counties and collected a total of 212 posts and 505 comments related to the HPV vaccine. The posts were published between 2010 and 2021, with the majority (83%) published after 2017. There were large variations of Facebook activities across counties. We categorized four counties with HPV vaccination initiation rates below 40% as low-coverage counties and five with rates above 40% as high-coverage counties. Low-coverage counties had less Facebook activities in comparison to high-coverage counties. Results showed on average comments about the HPV vaccine exhibited more positive emotion, more negative emotion, and more anger than the posts. Overall, thematic topics that emerged from posts centered around awareness and screening of HPV and cervical cancer, STI testing services, information sources, and calls to action for health services. However, comment topics did not correspond to posts and mostly were related to vaccine hesitancy, discussing vaccine risks, safety concerns, and distrust in vaccine science, citing misinformation. When comparing high- versus low-coverage counties, posts expressed similar sentiments; however, comments within high-coverage counties expressed more anger than in low-coverage counties. Comments from both high- and low-coverage counties expressed concerns with vaccine safety, risks, and injury. It is important to note that commenters exchanged information sources and tried to address misinformation themselves. Our results suggest the promotion of HPV vaccines from public Facebook pages and groups is limited in frequency and content diversity. This illustrates problems with generalized social media vaccination promotion without community tailoring and addressing specific hesitancy concerns. Public health agencies should listen to targeted audiences’ thoughts reflected through comments and design relevant messages to address these concerns for HPV vaccination promotion.